(untitled) (MAUSAM, 2014)
Climate is a primary determinant of agricultural productivity. In turn, food and fibber production is essential for sustaining and enhancing human welfare. The trends of maximum atmospheric temperature, rainfall are analysed for meteorological data of Anand district in Central Gujarat India. Rainfall distribution over India is highly erratic and uncertain both in time and space. Heavy rainfall for short period and some times continuous dry spell creates problems for crop growth. Therefore, it is necessary to study the rainfall analysis for developing farming system which may help to increase and stabilize agricultural production through better use of natural resources. Monthly rainfall over Anand showed increasing trend in August and September with decreasing trend in June and July. Such trend was more evident in since in 1971 onwards. It revealed that the monthly rainfall during July decreasing trend while August and September is in increasing trend. Such phenomenon was more evident since 1971 onwards. The positive value of Mann-Kendall test statistic (0.459) indicated that rainfall during southwest monsoon season had an increasing trend tendency which was significant in 0.05 levels. The rainfall of August was highly variable and undependable followed by September. The occurrence of excess and deficient rainfall when compared to that of normal was seen in more or less equal numbers of years. The rainfall range and its variability was less during deficient rainfall years when compared to that of excess rainfall years. During June month, the rainfall series showing significant (0.05) level in sub periods 1961-1990 (-0.340). In July month the series is showing significant level in sub periods like 1901-1930 (0.261), 1931-1960 (0.483) and 1961-1990 (0.261). In the August month the series is showing significant level in sub periods like 1931-1960 (0.655) and 1991-2011 (0.853). In the month of September the rainfall series is showing the significant level in sub periods like 1901-1930 (0.335), 1931-1960 (0.596) and 1991-2011(0.389).